2020
DOI: 10.1001/jamanetworkopen.2020.19861
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Recurrent Dupuytren Contracture Treatment

Abstract: IMPORTANCE Owing to its tendency to recur, Dupuytren contracture often requires multiple treatments, which places additional economic burden on health care. The likelihood of contracture recurrence varies not only with treatment but also with disease characteristics, such as contracture severity and location, but prior cost-effectiveness analyses of Dupuytren contracture treatments have not considered these patient-specific disease characteristics. OBJECTIVE To identify the most cost-effective treatment regime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Recurrences were reported in 160 of 199 digits (80%) at an average of 7.2 years after collagenase injection despite a heterogeneous patient population 17 . Furthermore, Yoon et al simulated recurrent DC in a 60-year-old patient and concluded that collagenase injections are not a cost-effective intervention and should not be preferred over percutaneous needle aponeurotomy or limited fasciectomy 18 . Leafblad et al retrospectively reviewed 848 interventions for DC, and reported 2-year reintervention rates following needle aponeurotomy, collagenase, and fasciectomy of 24%, 41%, and 4%, respectively, and 5-year rates of 61%, 55%, and 4%, respectively 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Recurrences were reported in 160 of 199 digits (80%) at an average of 7.2 years after collagenase injection despite a heterogeneous patient population 17 . Furthermore, Yoon et al simulated recurrent DC in a 60-year-old patient and concluded that collagenase injections are not a cost-effective intervention and should not be preferred over percutaneous needle aponeurotomy or limited fasciectomy 18 . Leafblad et al retrospectively reviewed 848 interventions for DC, and reported 2-year reintervention rates following needle aponeurotomy, collagenase, and fasciectomy of 24%, 41%, and 4%, respectively, and 5-year rates of 61%, 55%, and 4%, respectively 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent level II evidence for 5-year recurrence (defined as a 30degree increase in passive extension deficit) indicates that the combined recurrence of PIP and MCP joint contracture is 84.9, 32, and 21% for needle aponeurotomy, collagenase injection, and open fasciectomy, respectively. 69…”
Section: Outcomes Data On Dupuytren's Diseasementioning
confidence: 99%
“…The rapid increase in global life expectancy indicates that joint contractures and osteoarthritis (OA), the most common joint diseases in the elderly population [ 1 , 2 ], are becoming major global public health issues [ 3 ]. Joint contractures are present in more than 20% of elderly residents in long-term care facilities (LTCFs), and more than 10% develop symptoms of OA [ 1 ].…”
Section: Introductionmentioning
confidence: 99%